THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, REFERENCE GROUPS FOR REPURCHASE INTENTION IN A KOPI GAPTEK SURABAYA - Mochammad Chavi Abdullah; Joko Suyono (Journal of World Conference (JWC), 2019)
The intention to repurchase is the intention to repurchase a product twice or better for the same or different products. Therefore this study aims to analyze whether product quality, service quality, and reference groups can influence consumers' repurchase intention to buy gaptek coffee shop products located in jl. dinoyo. This research is quantitative research with a sample of 160 respondents. Furthermore, the data were analyzed using multiple linear regression analysis techniques and classical assumption tests. The results showed that three hypotheses showed 1 was not significant (product quality) and the other showed significance.